2014
DOI: 10.1371/journal.pone.0112972
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Complex 2 Signaling Pathway Regulates Transient Receptor Potential Cation Channel 6 in Podocytes

Abstract: Transient receptor potential cation channel 6 (TRPC6) is a nonselective cation channel, and abnormal expression and gain of function of TRPC6 are involved in the pathogenesis of hereditary and nonhereditary forms of renal disease. Although the molecular mechanisms underlying these diseases remain poorly understood, recent investigations revealed that many signaling pathways are involved in regulating TRPC6. We aimed to examine the effect of the mammalian target of rapamycin (mTOR) complex (mTOR complex 1 [mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…mTORC2 positively regulated TRPC6 in podocyte resulting in a massive calcium influx, which disrupted the filtration barrier, promoted the rearrangement of the highly dynamic podocyte actin cytoskeleton, and induced proteinuria. Inactivation of the Rictor/mTORC2 axis suppressed TRPC6 expression and decreased Ca + influx into the podocytes, thus reducing injury (14). In line with the latter observation, we demonstrated that HG/hyperglycemia is associated with activation of the Rictor/ mTORC2 signaling pathway and resulted in podocyte injury as assessed by a decrease in podocin expression and induction of podocyte loss/apoptosis.…”
Section: Fig 5 (Continued)supporting
confidence: 86%
See 2 more Smart Citations
“…mTORC2 positively regulated TRPC6 in podocyte resulting in a massive calcium influx, which disrupted the filtration barrier, promoted the rearrangement of the highly dynamic podocyte actin cytoskeleton, and induced proteinuria. Inactivation of the Rictor/mTORC2 axis suppressed TRPC6 expression and decreased Ca + influx into the podocytes, thus reducing injury (14). In line with the latter observation, we demonstrated that HG/hyperglycemia is associated with activation of the Rictor/ mTORC2 signaling pathway and resulted in podocyte injury as assessed by a decrease in podocin expression and induction of podocyte loss/apoptosis.…”
Section: Fig 5 (Continued)supporting
confidence: 86%
“…MTORC2 SIGNALING IN DIABETIC NEPHROPATHYtransient receptor potential cation channel 6 (TRPC6) (14). mTORC2 positively regulated TRPC6 in podocyte resulting in a massive calcium influx, which disrupted the filtration barrier, promoted the rearrangement of the highly dynamic podocyte actin cytoskeleton, and induced proteinuria.…”
Section: Fig 5 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mTORC1 activation predominantly at Ser2448 leads to the phosphorylation of its downstream target p70S6K, while the mTORC2 activation predominantly at Ser2481 leads to the phosphorylation of Akt at Ser473 [14,17]. In ADR-treated podocytes, the phosphorylation of mTOR at Ser2481 increased significantly in a time-dependent manner, whereas the phosphorylation of mTOR at Ser2448 showed no change ( Fig.…”
Section: The Mtorc2 Activation Is Related To Adr-induced Podocyte Apomentioning
confidence: 89%
“…Recently, it was reported that the inhibition of mammalian target of rapamycin (mTOR), can regulate TRPC6 expression in cultured normal podocytes [14,15]. The serine/threonine kinase mTOR forms two distinct functional complexes, mTORC1 and mTORC2 [16].…”
Section: Introductionmentioning
confidence: 99%